Implementasi Pembelajaran Berbasis Nilai Karakter pada Mahasiswa - Kardiana Metha Rozhana; Muhammad Fauzi Emqi; Moh Farid Nurul Anwar (Jurnal Bidang Pendidikan Dasar, 2022)
Character education is the most important thing in realizing a good attitude for prospective teachers in the Faculty of Education. Efforts are made starting from academic and non-academic activities. These students are equipped with existing faculties in the faculties in terms of how to speak, dress, and act. The purpose of this study is to describe the activities that exist in the faculty related to how to grow character values ​​on a populist campus. the average value in the Class of 2020 as many as 72.16% of students have a good attitude in the learning process. While the highest score was obtained in the 2021 batch as many as 77% of students had a good attitude. The questionnaire that was developed is one way to measure the character of each individual student. Efforts to cultivate characterful behavior must continue to be realized by supporting lecturers at the Faculty of Education.